PROFIL SENYAWA VOLATIL SELAMA FASE PERKEMBANGAN DAN SENYAWA KUNCI AROMA BUAH MELON (Cucumis melo L.) KULTIVAR GAMA MELON PARFUM - , UMAR HAFIDZ ASY'ARI HASBULLAH ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Melon (Cucumis melo L.) cv. Gama Melon Parfum (GMP) is a new melon cultivar made by cross breeding between female NO3 and male MR5 parents with prominent pleasure of aroma at ripening stage. During development stages, change in morphology and physiology characteristic might affected the volatile compounds production. Therefore, the volatile compounds profile during GMP-fruit developments, aroma compounds profile and key aroma identification and the physico-chemical characteristics were studied. Physico-chemical analysis were conducted on fruits harvested at 1, 2, 3, 4, and 5 weeks after pollination, while volatile compounds analysis was conducted on fruit after 5 weeks storage at -20Â°C. Results indicated that several volatile compounds were changed during fruit development, consisted of 8 esters, 2 alcohols 1 acid 3 terpenoids, and 3 hydrocarbons. Fruit volatile compounds profile was dominated by esters, followed by alcohol and acid, respectively. Interestingly, GMP melon key aroma characteristic were highly affected by the present of 3-penten-2-ol, acetic acid hexyl ester and 2-butanon-3-hydroxy. Physical properties was significantly changed during fruits development . Changing on chemical properties reflected by increasing of total soluble solid (TSS) and TSS:TA ratio, decreasing titratable acidity (TA) and pH during ripening stage.